"Boys indifferent to the manly sports of their race": nationalism and children's sport in Ireland, 1880–1920. Issue 3 (3rd July 2019) - McElligott, Richard
ABSTRACT: The late nineteenth century saw Irish children being exposed to formal sport in an unprecedented fashion. This era coincided with Ireland's so-called Gaelic Revival and the emergence of a virulent nationalism that helped fuel the Irish Revolutionary period which followed. Yet little research has been conducted on how nationalists used sport in their efforts to entice children into their campaigns for Ireland's cultural and political independence. This study examines the part which sport, particularly Gaelic games, played in attempts to inspire devotion to the ideal of an Irish-Ireland among the nation's children. It explores the efforts to promote native sports as the games of choice for children across the school grounds and playing fields of Ireland and the influence of nationalist media propaganda in this endeavour. Finally, it considers the role of sport in the training and physical culture of an array of Irish youth movements which arose at this time.